Is High Blood Pressure Self-Protection for the Brain?. Issue 12 (9th December 2016) - Warnert, Esther A.H.; Rodrigues, Jonathan C.L.; Burchell, Amy E.; Neumann, Sandra; Ratcliffe, Laura E.K.; Manghat, Nathan E.; Harris, Ashley D.; Adams, Zoe; Nightingale, Angus K.; Wise, Richard G.; Paton, Julian F.R.; Hart, Emma C.
Abstract : Rationale: : Data from animal models of hypertension indicate that high blood pressure may develop as a vital mechanism to maintain adequate blood flow to the brain. We propose that congenital vascular variants of the posterior cerebral circulation and cerebral hypoperfusion could partially explain the pathogenesis of essential hypertension, which remains enigmatic in 95% of patients. Objective: : To evaluate the role of the cerebral circulation in the pathophysiology of hypertension. Methods and Results: : We completed a series of retrospective and mechanistic case-control magnetic resonance imaging and physiological studies in normotensive and hypertensive humans (n=259). Interestingly, in humans with hypertension, we report a higher prevalence of congenital cerebrovascular variants; vertebral artery hypoplasia, and an incomplete posterior circle of Willis, which were coupled with increased cerebral vascular resistance, reduced cerebral blood flow, and a higher incidence of lacunar type infarcts. Causally, cerebral vascular resistance was elevated before the onset of hypertension and elevated sympathetic nerve activity (n=126). Interestingly, untreated hypertensive patients (n=20) had a cerebral blood flow similar to age-matched controls (n=28). However, participants receiving antihypertensive therapy (with blood pressure controlled below target levels) had reduced cerebral perfusion (n=19). Finally, elevated cerebral vascular resistance was a predictor of hypertension, suggesting that it may be a novel prognostic or diagnostic marker (n=126). Conclusions: : Our data indicate that congenital cerebrovascular variants in the posterior circulation and the associated cerebral hypoperfusion may be a factor in triggering hypertension. Therefore, lowering blood pressure may worsen cerebral perfusion in susceptible individuals. Abstract : Supplemental Digital Content is available in the text.